Comparison between the Outcomes of Water Birth and Normal Vaginal Delivery - Mitra Kolivand; Afshin Almasi; Sousan Heydarpour (Mashhad University of Medical Sciences, 2014)
Background & aim: Warm water immersion during labor is associated with relaxation and pain reduction for pregnant women. This method is not extensively used in Iran, given the fear of infection and other maternal/neonatal complications. Alternative methods are required to increase the safety of normal vaginal delivery. The purpose of this study was to compare maternal and neonatal outcomes, associated with water birth and normal vaginal delivery. Methods:This analytical, cross-sectional study was performed on 43 water birth cases (study group) and 62 subjects with normal vaginal delivery (control group). Random sampling and consensus were applied for normal vaginal delivery and water birth groups, respectively. Data were collected in a data collection form, using hospital records and interviews with mothers. For data analysis, descriptive and analytical tests including t-test and Chi-square were carried out, using SPSS version 15. Results: No significant difference was observed between the two groups in terms of labor and delivery complications; although three cases of complications during the second stage of labor and four cases of hospitalizations at birth were reported in the control group. The two groups were not significantly different in terms of hospitalization for the reason of neonatal period complications. Regarding maternal complications, there was a significant difference in the rate of episiotomy between the two groups (P=0.032). Postpartum hemorrhage was mostly observed in the control group, although the difference was not significant. Conclusion: In this study, no significant difference was observed in terms of maternal or neonatal complications between the two groups. Therefore, it seems that water birth is a safe method, associated with improved pregnancy outcomes.